Strategi pemasaran dalam meningkatkan penjualan UMKM Cipta Rasa Bakso Jeletot Kabupaten Kuningan Jawa Barat - Gufron, Ade; Rahmawati, Nur Fitri (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Through this analysis, it is hoped that concrete recommendations and solutions can be produced that can help Bakso Jeletot and similar MSMEs to design and implement effective digital marketing strategies, increase competitiveness, and face ever-growing market dynamics. Thus, it is hoped that this research can make a positive contribution to the development of MSMEs using social media. The aim of the research is to analyze marketing strategies in increasing sales of Jeletot meatball UMKM in Kuningan Regency, West Java, then to analyze the obstacles to marketing strategies in increasing sales of Jeletot meatball UMKM in Kuningan Regency. , West Java and to analyze marketing strategy solutions in increasing sales with MSMEs Jeletot Meatballs in Kuningan Regency, West Java Research Method using Qualitative. Number of informants 4. Results of research on Jeletot Meatball Prices in determining prices are appropriate, Jeletot meatball products have met targets with making distinctive meatballs and sauce according to customer tastes. The place is good because it has a sense of security and comfort in accordance with the factors taken into consideration when choosing a location. And in terms of promotion of Bakso Jeletot there is still a lack of promotion in social media from Advertising, Public Relations and Sales Promotion for Personal Selling which has been carried out using WhatsApp. The marketing strategy obstacle faced by Cipta Rasa Bakso Jeletot in increasing sales is the price constraint, namely the lack of price cuts or discounts, then there are problems with the product, namely that it is not popular with all groups, only spicy lovers and adults, then there are fluctuating raw materials, and finally, regarding promotion, the obstacle faced by Cipta Rasa Bakso Jeletot is a lack of social media management, video and image editing. The marketing strategy solution carried out by Cipta Rasa Bakso Jeletot is to deliver at certain hours and provide cashback for payments using e-wallet, then the solution for the product is to provide other menu options, then for raw materials, contracts are given to raw material suppliers and finally the solution is for promotions, carrying out professional rentals. editors in carrying out everything from social media management to content creation due to the limited capital available at Cipta Rasa Bakso Jeletot requiring budgeting for promotion.